The Key Target and Molecular Mechanism of the Volatile Component of Scutellaria baicalensis Georgi in Acute Lung Injury Based on Network Pharmacology - Zhu, Guosong; Zhang, Jiaqiang; Yang, Yali; Zhang, Haoran; Jin, Wenwen; Su, Fangchu; Liang, Junting; Wang, Kaiwei; Zhang, Jianhua; Chen, Chuanliang (Frontiers in Pharmacology, 2021)
Ethnopharmacological relevance: Scutellaria baicalensis georgi is one of the most widely studied TCMs that a large number of experiments were shown to have effects in ALI; The efficacy of volatile oil from TCM remains to be studied. Aim: The volatile component of Scutellaria baicalensis georgi was selected to act on the key target of acute lung injury and was preliminarily studied for its specific molecular mechanism. Methods: The volatile active substances of Scutellaria baicalensis georgi were extracted by GC–MS, and the active ingredients related with the occurrence and development of acute lung injury were searched and matched by the TCMSP database. The pharmacologic data and analysis platform of TCM were used to retrieve and screen for the volatile active components and the possible therapeutic targets of S. baicalensis georgi. In addition, acute lung injury was searched in the disease target database to identify the corresponding disease target proteins, thereby, establishing a protein–protein interaction network. Finally, the effects of wogonin on the apoptotic and inflammatory factors in the acute lung injury cell model were analyzed experimentally. Results: We identified 100 candidate targets and successfully constructed a complex target network. The targets identified by the above gene enrichment analysis played important roles in the autoimmune disease cell cycle apoptosis and related signaling pathways. KEGG pathway analysis showed that most of the target genes were involved in the inflammatory response regulation of the TRP, PI3K-Akt, and IL-17 signaling pathways. The participation of wogonin in the specific regulatory pathways of PI3K-Akt signaling and IL-17 signaling was verified through experiments. In the lung injured cell model, the results showed that wogonin inhibited the apoptosis of injured lung cells by inhibiting the expression of BAD gene and the activation of cleaved caspase-3 gene while increasing Bcl-2 expression. In addition, wogonin inhibited the expression of the above-mentioned inflammatory factors and further inhibited the inflammatory response in the lung injury cells. Conclusion: Wogonin may protect the pulmonary vascular endothelial cells and inhibit the progression of lung injury by reducing the apoptosis of pulmonary bronchial epithelial cells and downregulating the secretion of inflammatory factors.